Assessing the risk of an anomalous circumflex artery using balloon aortic valvuloplasty prior to transcatheter aortic valve replacement. Issue 2 (20th January 2020) - Tabachnick, Deborah; Obokhae, Brigette; Harrington, Katherine; Brown, David L.
Abstract: Anomalous origin of the left circumflex coronary artery from the right sinus of Valsalva or proximal right coronary artery (RCA) is a well‐known anatomic variation. Although the condition is usually benign, there is risk for compression of the anomalous artery by a prosthetic valve in patients undergoing aortic valve replacement (AVR). In more recent years, balloon aortic valvuloplasty (BAV) has been performed prior to transcatheter aortic valve replacement (TAVR) to serve as a diagnostic tool in the evaluation of symptom relief and procedural risks prior to definitive therapy with TAVR. However, the literature regarding BAV utilization in the assessment of coronary artery anomalies prior to TAVR is scarce. Our case illustrates the importance of performing preoperative BAV to assess the safety of a TAVR procedure in patients with coronary anomalies. Herein, we present a case of a patient who underwent BAV with selective angiography of her anomalous circumflex artery. During balloon inflation, the anomalous circumflex artery was transiently occluded, with complete resolution with balloon deflation. Given these findings, the patient was deemed to be unsuitable for TAVR and offered surgical AVR. This case demonstrates that patients with anomalous coronary circulation may require BAV with selective angiography to fully evaluate risk of coronary occlusion with TAVR.